Technical note: allocation of optimal tolerances in a mechanical assembly using DE and NSGA-II. (9th February 2010) - Sivakumar, K.; Balamurugan, C.
This paper discusses a general methodology based on evolutionary algorithms (Elitist Non-dominated Sorting Genetic Algorithm (NSGA-II) and Differential Evolution (DE)) for allocation of optimal tolerance for an over-running clutch assembly. New hybrid models are developed for obtaining the manufacturing costs of hub, rollers and cage. The aim of this paper is to find optimal tolerances values that give minimum combined objective function value, minimum Manufacturing Cost (MC), minimum Quality Loss (QL) function and maximum Number of Standard Deviations (ZNSD) by satisfying stack-up conditions using non-traditional optimisation techniques. The results obtained from various techniques are compared and analysed.